Analisis Kesulitan Membaca Bagi Anak Berkebutuhan Khusus (Disleksia) - Lestari, Yuni; Elhefni, Elhefni; Rohadi Wibowo, Djoko (Program Studi PGMI, Universitas Al Falah As Sunniyah Kencong Jember, 2023)
The background of this research is that there are still many reading difficulties experienced by children with special needs with dyslexia. This happens because of the lack of more attention that teachers should give to dyslexic students, and also because there are several factors such as biological, cognitive, and problems in social relationships that cause children to experience dyslexia. The aims of this research are (1) to find out reading difficulties for dyslexic children at Pembina State SLB Palembang, (2) to find out the factors that influence reading difficulties for dyslexic children at Pembina State SLB Palembang, (3) to find out efforts teachers in overcoming reading difficulties for dyslexic children at Pembina Palembang State SLB. The type of this research is qualitative research with a qualitative descriptive approach. The results of this study are as follows. (1) There are three dyslexic students at the school, namely student D, student S, and student R. The difficulty in reading for dyslexic children at the Pembina Palembang State Special School is that there are three dyslexic students at the school, namely student D, student S, and student R. Students D & S students have difficulty distinguishing letters and numbers (directional dyslexia), and can only read if they read one letter at a time to understand their meaning (Spelling Dyslexia). Meanwhile, student R has difficulty in spelling words into syllables (Phonological Dyslexia). (2) Factors that influence reading difficulties for dyslexic children at SLB Pembina Palembang are environmental factors, lack of motivation to practice, and lack of interest in learning. (3) The teacher's efforts in overcoming reading difficulties for dyslexic children at Pembina Palembang State Special School are using the letter recognition method, using the image method, and paying special attention, both through special learning after KBM and parental guidance and motivation at home.